2022
DOI: 10.3390/su14052542
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and Analysis of Power-Regenerating Potential for High-Speed Train Suspensions

Abstract: Sustainable technologies in transport systems have attracted significant research efforts over the last two decades. One area of interest is self-powered devices, which reduce system integration complexity and cost with an undoubtedly great potential for improving adaptability and developing sustainability in railway transport systems. One potential solution is a regenerative suspension system, which enables the suspension movements and dissipated energy to be converted into useful electricity. This paper expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Liu Jun designs an operation scheduling system based on decentralized self-regulation, defines and explains the structure, knowledge expression, and reasoning methods of each intelligent body, and proposes a decision system consisting of a five-layer network for solving railroad operation scheduling problems [14]. Chen Xiaowei and Shen Chenglu use CAN bus technology and industrial Ethernet technology to realize a distributed computer interlocking system integrating signal machine intelligent body, turnout intelligent body, and section intelligent body [15]. Taking Beijing South…”
Section: State Of the Artmentioning
confidence: 99%
“…Liu Jun designs an operation scheduling system based on decentralized self-regulation, defines and explains the structure, knowledge expression, and reasoning methods of each intelligent body, and proposes a decision system consisting of a five-layer network for solving railroad operation scheduling problems [14]. Chen Xiaowei and Shen Chenglu use CAN bus technology and industrial Ethernet technology to realize a distributed computer interlocking system integrating signal machine intelligent body, turnout intelligent body, and section intelligent body [15]. Taking Beijing South…”
Section: State Of the Artmentioning
confidence: 99%
“…Abdelkareem et al (2019) demonstrated that the potential power of a full-load truck suspension is about 71–434 W and 287–1733 W on class C and D roads. Wang et al (2022) theoretically assessed the power potential of the primary and secondary suspensions of high-speed railway trains. The results showed that the ERSA could generate 5–30 W and 5–45 W when installed on the primary and secondary dampers, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In [31], a finite element model of rigid overhead systems using Ansys is developed, and the authors highlight that the The expansion of electric railway networks around the world brings a number of technical challenges to academia and industry [4][5][6]. The interaction of the pantograph-contact wire is one of the urgent issues in railway dynamics [7,8], as it directly affects the current collection quality of the train. In recent times, several scholars have directed their focus and efforts towards researching the performance of pantograph-contact wire interactions.…”
Section: Introductionmentioning
confidence: 99%